Microstructural evolution in a superelastic metastable beta-Ti alloy. (February 2017) - Coakley, James; Isheim, Dieter; Radecka, Anna; Dye, David; Stone, Howard J.; Seidman, David N.
Abstract: The microstructural evolution of Ti-24Nb-4Zr-8Sn wt.% during low-temperature ageing is examined by atom-probe tomography (APT) and X-ray diffraction (XRD). This ageing is deleterious to the desirable mechanical properties, such as ultra-low elastic modulus and superelasticity. Initially, the cold-rolled alloy possesses a martensitic α ′′ -precipitate/ β -matrix microstructure. On ageing, Ti-rich/solute-lean precipitates grow in linear arrangements, which are likely associated with dislocations. Additionally, the composition and number density of Nb-rich domains (which are associated with superelasticity) are quantified for the first time. The domains are unstable, but decrease in number density during ageing, causing the deterioration in mechanical properties. Graphical Abstract: Ti-24Nb-4Zr-8Sn wt.% (Ti-2448) APT reconstructions of a Ti 85.5 at.% isoconcentration surface (blue) and Nb 22.8 at.% isoconcentration surface (red) for a) Ti-2448 + 300 °C/4 h age, and b) Ti-2448 + 300 °C/8 h age, with 25% of the Zr atoms displayed (purple). Highlights: The Ti-rich/solute-lean precipitates ω and α precipitates (blue) form in linear arrangements that likely are associated with dislocations. The Ti-lean/Nb-enriched domains (red) are unstable, and decrease in number density with ageing time. The dissolution of the Nb-rich domains at 300 °C is identified as the cause of deterioration of the elastic properties.